Prevalence of cardiovascular risk factors in an urban ambulatory adult population: AsuRiesgo study, Paraguay - Chaves, Graciela; Brítez, Nidia; Maciel, Victor; Klinkhof, Andreas; Mereles, Derliz (Revista panamericana de salud pública, 2015)
OBJECTIVE: Cardiovascular diseases are the leading cause of mortality in the world. Although most of them are preventable, their prevalence continues to increase. The objective of this study was to estimate the prevalence of cardiovascular risk factors in an urban ambulatory adult hospital population in Asunción, Paraguay. - METHODS: A cross-sectional study was undertaken in the population of patients enrolled in the AsuRiesgo prospective study on the prevention of cardiovascular disease, which focuses on promoting a healthy lifestyle. Patients 18 years of age or older who were encountered in doctors' waiting rooms in a tertiary care hospital were invited to participate. Each patient's clinical history, body measurements, and laboratory test results were obtained. - RESULTS: A total of 18 287 patients aged 51 ± 16 years were recruited. Of this group, 67.5% were female, with an average bodyweight of 77.5 ± 16.2 kg and a body mass index 29.7 ± 5.9 kg/m². The prevalence rates of a history of myocardial infarction, stroke, diabetes mellitus, and hypertension were 2.6%, 3%, 13.3%, and 53%, respectively, and the rates of smoking, unhealthy diet, sedentary lifestyle, and psychological stress were 29.3%, 41.2%, 58.2%, and 56.6%. The overall prevalence of obesity and overweight was 79.6%; the rates of prehypertension and systemic hypertension were 39% and 25%, respectively; and the prevalence of metabolic syndrome was 34.7%. - CONCLUSIONS: Although the prevalence rates of smoking, systemic hypertension, and diabetes mellitus were low, those for obesity, sedentary lifestyle, psychological stress, unhealthy diet, and metabolic syndrome were very high. This finding demonstrates the need for global action to prevent disability and death from ischemic heart and cerebrovascular disease. It is urgent to implement programs to address these challenges on a national scale.
Gesehen am 13.11.2020
keine DOI